2017
DOI: 10.1002/2016jc012197
|View full text |Cite
|
Sign up to set email alerts
|

Improved forecasts of winter weather extremes over midlatitudes with extra Arctic observations

Abstract: Recent cold winter extremes over Eurasia and North America have been considered to be a consequence of a warming Arctic. More accurate weather forecasts are required to reduce human and socioeconomic damages associated with severe winters. However, the sparse observing network over the Arctic brings errors in initializing a weather prediction model, which might impact accuracy of prediction results at midlatitudes. Here we show that additional Arctic radiosonde observations from the Norwegian young sea ICE exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 53 publications
(68 reference statements)
2
55
0
Order By: Relevance
“…; Sato et al . ), these have tended to focus on a single observation type and were conducted in assimilation systems that used fewer observations than would be common in current operational NWP, with very limited usage of satellite data in particular. To our knowledge, this is therefore the first time that comprehensive numerical experimentation has been carried out to explore the role of different Arctic observing systems in a state‐of‐the‐art NWP system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Sato et al . ), these have tended to focus on a single observation type and were conducted in assimilation systems that used fewer observations than would be common in current operational NWP, with very limited usage of satellite data in particular. To our knowledge, this is therefore the first time that comprehensive numerical experimentation has been carried out to explore the role of different Arctic observing systems in a state‐of‐the‐art NWP system.…”
Section: Introductionmentioning
confidence: 99%
“…This assessment relies on extensive numerical experimentation with the ECMWF Integrated Forecasting System (IFS), which is used operationally to produce global weather forecasts at scales from days to months. Although studies on the impact of Arctic observations on Arctic and midlatitude weather forecasts have been carried out previously (e.g., Inoue et al, 2013;Sato et al, 2017), these have tended to focus on a single observation type and were conducted in assimilation systems that used fewer observations than would be common in current operational NWP, with very limited usage of satellite data in particular. To our knowledge, this is therefore the first time that comprehensive numerical experimentation has been carried out to explore the role of different Arctic observing systems in a state-of-the-art NWP system.…”
Section: Introductionmentioning
confidence: 99%
“…Such experiments can also be used to quantify the impact of specific Arctic observations on the initial conditions in the Arctic, and subsequently on the forecast skill in the midlatitudes. However, until recently such OSEs have only been performed for Arctic observations in a reduced complexity forecasting system (Sato et al, 2018) and have tended to focus on specific case-studies, such as cold air outbreaks (Sato et al, 2017). As a result, they are not necessarily representative of what one might find in a comprehensive operational global NWP system, such as the Integrated Forecasting System (IFS) of the European Centre for Medium-range Weather Forecasts (ECMWF).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of such errors can be reduced not only by improvement of model performance but also by an increase in the quantity of observational data that is combined with the forecast data. Using observing system experiments (OSEs), previous studies have demonstrated that incorporation of additional Arctic radiosonde observations can influence the reproduction of atmospheric circulation of upper-level troughs in analyses and weather forecasts over the Northern Hemisphere Kristjánsson et al, 2011;Yamazaki et al, 2015;Sato et al, 2017Sato et al, , 2018a. Incorporation of Arctic drifting buoy data reduces the uncertainty (ensemble spread) of simulated sea level pressure (SLP) over sea ice; however, the effect has been limited to the lower troposphere .…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of Arctic drifting buoy data reduces the uncertainty (ensemble spread) of simulated sea level pressure (SLP) over sea ice; however, the effect has been limited to the lower troposphere . Additional Arctic radiosonde observations, which reduce the ensemble spread at the upper levels in analysis data, have improved the accuracy of forecasts of surface circulation over the Arctic Ocean (Kristjánsson et al, 2011;Yamazaki et al, 2015; and of midlatitude cyclones (Sato et al, 2017;2018a). In contrast, few studies have conducted OSEs using Antarctic observations, where the impact of additional radiosonde observations would be expected to extend over a wide area because of the lack of data near the South Pole (Semmler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%